2021
DOI: 10.1029/2021ja029710
|View full text |Cite
|
Sign up to set email alerts
|

Statistics on Jupiter’s Current Sheet With Juno Data: Geometry, Magnetic Fields and Energetic Particles

Abstract: Jupiter, the fifth planet from the sun, has the strongest intrinsic magnetic field among planets in the solar system. The interplay between this magnetic field and the solar wind results in a magnetosphere extending from the topside of Jupiter's atmosphere/ionosphere to beyond 𝐴𝐴 𝐴𝐴∼ 100 𝐴𝐴 R𝐽𝐽 (1 𝐴𝐴 R𝐽𝐽 = 𝐴𝐴 ∼ 71,400 km, Jupiter radii; hereinafter, 𝐴𝐴 𝐴𝐴 represents the radial distance to the Jupiter) (Bagenal et al., 2007). Jupiter's magnetosphere is filled with plasma originating from vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 41 publications
3
37
1
Order By: Relevance
“…While EMIC waves have been observed at Jupiter inside perhaps L = 13 RJ (Lin et al, 1993), we have found no published record of EMIC waves in the trans-Ganymede region. Mauk and Krimigis (1987) using dayside Voyager-1 data, the colored diamonds and circles were determined using the Juno magnetometer data during the nightside perijove 31 (PJ31) using the procedures developed in Mauk and Krimigis (1987), and the blue squares are from an analysis of the statistical results of Liu et al (2021) for the nightside (see text). (b) Alfvénic magnetic turbulence as measured by Galileo and reported by Saur et al (2003) at a reference frequency of 2.4 × 10 −3 Hz.…”
Section: What Causes Strong Scattering In the Trans-ganymede Region?mentioning
confidence: 99%
See 1 more Smart Citation
“…While EMIC waves have been observed at Jupiter inside perhaps L = 13 RJ (Lin et al, 1993), we have found no published record of EMIC waves in the trans-Ganymede region. Mauk and Krimigis (1987) using dayside Voyager-1 data, the colored diamonds and circles were determined using the Juno magnetometer data during the nightside perijove 31 (PJ31) using the procedures developed in Mauk and Krimigis (1987), and the blue squares are from an analysis of the statistical results of Liu et al (2021) for the nightside (see text). (b) Alfvénic magnetic turbulence as measured by Galileo and reported by Saur et al (2003) at a reference frequency of 2.4 × 10 −3 Hz.…”
Section: What Causes Strong Scattering In the Trans-ganymede Region?mentioning
confidence: 99%
“…(a) Equatorial radius of curvature of Jupiter's magnetic field configuration as a function of radial position normalized by radial position, and the normalized size of the ion gyroradii at the minimum magnetic field position for 100 keV H + , O + , and S + . The black points and curves were determined byMauk and Krimigis (1987) using dayside Voyager-1 data, the colored diamonds and circles were determined using the Juno magnetometer data during the nightside perijove 31 (PJ31) using the procedures developed inMauk and Krimigis (1987), and the blue squares are from an analysis of the statistical results ofLiu et al (2021) for the nightside (see text). (b) Alfvénic magnetic turbulence as measured by Galileo and reported bySaur et al (2003) at a reference frequency of 2.4 × 10 −3 Hz.…”
mentioning
confidence: 99%
“…The Juno spacecraft has high inclination orbits and observes energetic electron variations from the auroral region to the equator (Bagenal et al, 2017). Previous studies presented energetic electron fluxes at 𝐴𝐴 𝐴𝐴 𝐴 17 (Wang et al, 2021) and 𝐴𝐴 𝐴𝐴 𝐴 20 (Liu et al, 2021) near the magnetic equator, yet a global survey which would capture the two regions together, track the radial profile of electron phase space densities and study electron pitch angle distributions is needed to understand electron transport and acceleration in the plasma sheet and radiation belts. In this paper, we evaluate energetic (>100 MeV/G) electron distributions near the magnetic equator in Jupiter's plasma sheet ( 𝐴𝐴 𝐴𝐴 𝐴 20 ) and outer radiation belt ( 𝐴𝐴 𝐴𝐴 𝐴 20 ) using Juno observation during the first 29 orbits.…”
mentioning
confidence: 99%
“…Moreover, to compensate for the relative densities at the orbit of Ganymede, following the approach by Kivelson et al (2004), as in Plainaki et al (2020a), we applied a scaling factor of 1:5 to the fluxes above (science case (i)) and below (science case (iii)) the center of the JPS with respect to the denser center of the JPS itself. We note that this scaling factor represents an upper limit since recent studies based on Juno proton and electron data indicate a smoother gradient between omnidirectional energetic ion fluxes near the JPS and above it (e.g., Liu et al 2021). Our approach makes it easier to compare the current results with those in Plainaki et al (2020a); moreover, a change in the scaling of the fluxes as a function of Ganymede's magnetic latitude would only affect the absolute ion fluxes at 500 km and on the surface, not their ratio.…”
Section: Ion Velocity Distributionmentioning
confidence: 91%
“…As shown in Table 2, no dramatic differences in the H + fluxes in the vicinity of Ganymede exist between the calculations in Paranicas et al (1999) and Paranicas et al (2021). Liu et al (2021), however, argued that time variations are anyway large enough to account for changes in the spectra larger than the uncertainty induced by penetrating radiation. Their study reaches only down to 20 R J , slightly outward of Ganymede, but gives a good sense of time variations in the moon's vicinity.…”
Section: Model Descriptionmentioning
confidence: 94%